Motorcyle police pose with motorcycles - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of motorcycle police officers with their motorcycles. The officers are dressed in uniforms and are lined up next on the street. In the background is a large municipal building, possibly the police station headquarters. Two flags are displayed and one is the United States flag. Other buildings populate the background. One of the buildings on the far right is the Richfield and Richlube business. Tracks can be seen on the street coming from both the left and the right. Parked cars are visible on the street.